The Use of Social Networking Sites Influencing the Academic Performance of Students - Tiongson, Gideon (Journal of Interdisciplinary Perspectives, 2024)
This study investigated the impact of social networking site (SNS) usage on students' academic performance. It explored the frequency, purpose, and access to SNS alongside academic performance across four subjects (English, Science, Mathematics, and Filipino) over three grading periods. A descriptive- correlational research design was used, with data collected through questionnaires from purposively sampled Grade 7 to Grade 10 students. Statistical tools included mean, standard deviation, and Pearson correlation. Results showed occasional SNS use for specific purposes. Facebook was frequently used, YouTube occasionally, while Twitter, Myspace, and Instagram were rarely used. Students’ academic performance was generally satisfactory. A moderate relationship was found between Facebook usage and academic performance across all subjects, a low relationship with YouTube, and negligible relationships with Twitter, Myspace, and Instagram. Students reported enjoying entertainment activities like watching movies and celebrities and listening to music through SNS. Schools are encouraged to conduct time management and productivity workshops to help students balance academic and leisure activities effectively.